The Effects of Aloe vera Cream on the Expression of CD4+ and CD8+ Lymphocytes in Skin Wound Healing - Yos Adi Prakoso; Kurniasih (Journal of Tropical Medicine)
The aim of this study is to explore the effect of topical application of Aloe vera on skin wound healing. Thirty-six male Sprague-Dawley rats weighing 150–200 grams were divided into four groups. All groups were anesthetized, shaved, and exposed to round full-thickness punch biopsy on the back: group I (control); group II (treated with 1% Aloe vera cream); group III (treated with 2% Aloe vera cream); and group IV (treated with madecassol®). The treatments were given once a day. Macroscopic and microscopic examination were observed at 5, 10, and 15 days after skin biopsy. Skin specimens were prepared for histopathological study using H&E stain and IHC stain against CD4+ and CD8+ lymphocytes. All the data were analyzed using SPSS16. The result showed that topical application of 1% and 2% Aloe vera cream significantly reduced the percentage of the wound, leucocytes infiltration, angiogenesis, and expression of CD8+ lymphocytes and increased the epidermal thickness and the expression of CD4+ lymphocytes (p ≤ 0,05). There was no significant difference in the number of fibroblasts in all groups. Topical application of 1% and 2% Aloe vera cream has wound healing potential via their ability to increase the ratio of CD4+/CD8+ lymphocytes in the wound area.